PENGGUNAAN METODE BRANCH AND BOUND UNTUK MENYELESAIKAN MASALAH PENUGASAN PADA KASUS PENYUSUNAN JARINGAN KOMUNIKASI - Fitriadi Fitriadi; Dewi Sri Susanti; Nur Salam (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2010)
Assignment problem is how to match exactly only one agent for one task, the aim is to getmaximum advantage or minimum cost. One of assignment problem case is arrangingcommunication network, that how to make order formation of sending Short Massage Service(SMS) from someone to another one in a group. Each one in that group has to send one SMS to theother member. The last stage in this process is the SMS was sent by the first sender will comebackto the first sender again as indication that all of member of a group was received SMS.Arranging communication network is done by using branch and bound method by distributingthe big scale problem to the small until it can be solved. Distributing is done recursive until formedtree structure. The objective of this research is how to find optimal solution for solving assignmentproblem in arranging communication network by using branch and bound method.This research is done with literature study method that is by collecting and studying fromsupporter reference related to assignment problem and branch and bound method. Procedure inthis research that is forming cost matrix, reducing rows and columns, counting up all rows andcolumns reducer as bound of 0 node. 0 node have branch that called first level, node’s bound offirst level finding by using formula Cs = Cr + Ci,j + r. optimum bound of first level make as E-nodethat will branched and resulting second level, etc. The result of research is finding one of communication network that below: Simpati  AsHalo Matrix Mentari starOne Im3Flexi Fren XL Simpati with minimum costRp 1.298.